El sector privado como actor estratégico del posconflicto en Colombia (2017)
The territories affected by the armed conflict in Colombia suffer from difficulties in terms of economic, social and infrastructure matters. Taking into account, the recent peace agreement between Colombia's government and the FARC, as well as the country's economic moment, it's important to analyze the role of the private sector in the development of these territories. Therefore, this document analyzes the recent regulations and incentives that help bring growth into these territories. Specifically, the paper seeks to analyze an instrument called Obras por Impuestos and its applicability in Colombia.